An experimental investigation into the scattering properties of maximum length sequence diffusers and quadratic residue diffusers. (1st January 2022) - Pan, Lili; Zhao, Yuezhe
Abstract: Since the invention of Schroeder diffusers, extensive studies have been carried out on the prediction and measurement of diffusion coefficients and correlation scattering coefficients in the far field, providing valuable referring data for public. However, as another important evaluation index, the random-incidence scattering coefficients of Schroeder diffusers, which are popularly used in geometric room acoustic models for accurate predictions, have not yet been systematically studied in the diffusing field. This paper presents an experimental study on the scattering coefficients of two well-known Schroeder diffusers (maximum length sequence (MLS) diffusers and quadratic residue diffusers (QRDs)) in one 1:10 scaled-down reverberation room. The scattering coefficients of these Schroeder diffusers were compared to discover their variation laws as a function of well depth, well width, sequence length and the ratio of the maximum well depth to the wave length. To validate the accuracy and reliability of the scaled-down measurements, the scattering coefficients of six MLS diffusers, as well as their standard deviations, were also measured in a full-size reverberation room. The results measured in this study provide engineers and acousticians with some useful reference data in room acoustics design.